Platelet microparticles in cryopreserved platelets: Potential mediators of haemostasis. Issue 2 (October 2015) - Johnson, Lacey; Raynel, Sarah; Seghatchian, Jerard; Marks, Denese C.
Abstract: Platelet concentrates can be cryopreserved in dimethylsulphoxide (DMSO) and stored at −80 °C, which increases the shelf-life from 5 days to up to 4 years. Cryopreserved platelets have been shown to contain a high number of microparticles that have in vitro haemostatic activity. Further, when transfused, cryopreserved platelets have been shown to be at least as haemostatically active, as liquid-stored platelets, if not more so. Given that microparticles are traditionally considered to be pro-coagulant, it is likely that their presence in the cryopreserved component contributes to this haemostatic effect. However, as microparticles are known to mediate many physiological and pathological processes, including in thrombosis and cancer development and progression, further work is warranted to fully understand the functional scope of the microparticles in cryopreserved platelets.